Caged xanthones: Potent inhibitors of global predominant MRSA USA300 - Pongkorn Chaiyakunvat (2018)
© 2016 Elsevier Ltd. All rights reserved. Total of 22 caged xanthones were subjected to susceptibility testing of global epidemic MRSA USA300. Natural morellic acid showed the strongest potency (MIC of 12.5 μM). However, its potent toxicity diminishes MRSA therapeutic potential. We synthetically modified natural morellic acid to yield 13 derivatives (3a-3m). Synthetically modified 3b retained strong potency in MRSA growth inhibition, yet the toxicity was 20-fold less than natural morellic acid, permitting the possibility of using caged xanthones for MRSA therapeutic.